Coldplay Gate sebagai Cermin Ketimpangan Gender dan Etika Relasi di Dunia Kerja - Azizah Kurnia Anggraini; Nada Hafiyah Klariesha; Indah Rizki Bethania Silitonga; Olivia Diva Nabila; Dian Alya Julianti (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This study examines the Coldplay Gate phenomenon as a reflection of gender inequality and weak ethical relations in the workplace. The event, which began as a personal issue in the entertainment sphere, evolved into a public discourse because it revealed the vulnerability of women within organizational power structures. The workplace, which should uphold professionalism, instead demonstrates gender bias, subordination, and dysfunctional practices that undermine institutional integrity. This research employs a descriptive qualitative approach with a literature study as the main method. Data were collected from news articles, research reports, and official publications from both national and international institutions such as the World Bank Gender Data Portal (2024), Statistics Indonesia (BPS, 2024), the International Labour Organization (ILO), and Populix (2024). Data analysis was conducted using content analysis to identify key themes, including women’s subordination, abuse of power relations, and weak organizational ethics. The findings indicate that Coldplay Gate should not be understood merely as a personal scandal but as a reflection of unequal workplace structures. Empirical data reinforce this conclusion, such as women’s labor participation of only 55.41 percent, limited representation in strategic positions (15 percent of CEOs are women), and high levels of workplace discrimination (45 percent). These findings highlight the need for ethical awareness and gender sensitivity to be internalized within organizational culture. The study concludes that formal regulations must be accompanied by the development of a fair, safe, and inclusive professional culture, enabling workplaces to function as equal spaces for all individuals without barriers based on gender or power relations.